Play : a comedy, in four acts / by T.W. Robertson ; as first performed at the Prince of Wales's Theatre, London, under the management of Miss Marie Wilton, Feb. 15, 1868 ; to which is added a description of the costume, cast of the characters, entrances and exits, relative positions of the performers on the stage, and the whole of the stage business. - Robertson, T. W. (Thomas William), 1829-1871. (Tufts University. Tisch Library., 2015)
1 online resource (38 pages) : illustrations.; Electronic reproduction. Medford, MA : Tisch Library, Tufts University, 2015. Scanned by the Boston Library Consortium/Open Content Alliance as part of the BLC OCA Digitization Project from a copy at the Tisch Library, Tufts University.; Series: Sergel's acting drama ;no. 494.